A Structural Equation Model of Perceived Autonomy Support and Growth Mindset in Undergraduate Students: The Mediating Role of Sense of Coherence - Ma, Chunhua; Ma, Yongfeng; Lan, Xiaoyu (Frontiers in Psychology, 2020)
Although prior research has extensively documented the correlates of growth mindset, little is known about its antecedents in undergraduate students. Guided by the self-determination theory, the current study investigated the association of perceived autonomy support (i.e., parental autonomy support and teacher autonomy support) with growth mindset, and assessed whether sense of coherence mediated this association. A total of 1,030 Chinese undergraduate students (M age = 20.44; SD = 1.52; 62.4% females) aged from 18 to 25 years old were involved in this study; they were asked to fill in a set of self-reported questionnaires. Results from structural equation modeling showed that sense of coherence fully mediated the association between parental autonomy support and growth mindset, and between teacher autonomy support and growth mindset. More precisely, parental autonomy support and teacher autonomy support were each positively associated with sense of coherence, which in turn was positively related to growth mindset. The current findings confirm the beneficial effect of autonomy support on individuals’ adaptive skills in a collective cultural context, suggesting that autonomy-supportive parents and teachers can contribute to undergraduate students’ growth mindset through the role of sense of coherence.